Strategies for Developing Moral Values in Early Childhood Through Songs and Traditional Games: A Literature Review - Seni Yuliarini; Nur Cholimah (Universitas Sulawesi Barat, 2025)
In today's modern era, traditional songs and games are increasingly marginalized due to the dominance of popular culture and digital technology. This study aims to examine literature on strategies for developing moral values in early childhood through songs and traditional games, while exploring their implementation potential and challenges in early childhood education. Using a literature review methodology, the research analyzes 15 previous studies on moral development strategies through these traditional mediums. Content analysis was employed for data synthesis. Findings reveal that songs effectively build value comprehension through enjoyable repetition and positive emotional experiences, while traditional games enable children to practically apply these values in peer interactions. The study concludes that integrating both media in early childhood education can create meaningful, engaging learning environments with long-term positive impacts on children's moral development.